Situation Report: Hungary, 21 April 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. License and Patent Imports Unsatisfactory Measures to Increase Machinery Imports from the "Socialist" Countries French Trade Delegation Concludes Negotiations in Budapest CC Plenum Better Consumer Goods Supply for Lower-Income Groups Problems of Agricultural Modernization April Session of the National Council of Agricultural Producers' Co-Operatives Completion of the Nation-Wide Reorganization of "Weak" Farmers' Co-Operatives Death of Peter Veres and Mihaly Vaci